A clinical trial about effects of prebiotic and probiotic supplementation on weight loss, psychological profile and metabolic parameters in obese subjects. Issue 2 (6th January 2023) - Ben Othman, Rym; Ben Amor, Nadia; Mahjoub, Faten; Berriche, Olfa; El Ghali, Chaima; Gamoudi, Amel; Jamoussi, Henda
Abstract: Introduction: The management of obesity is difficult with many failures of lifestyle measures, hence the need to broaden the range of treatments prescribed. The aim of our work was to study the influence of pre and probiotics on weight loss psychological profile and metabolic parameters in obese patients. Methods: It is a clinical trial involving 45 obese patients, recruited from the Obesity Unit of the National Institute of Nutrition between March and August 2022 divided into three groups: diet only (low‐carbohydrate and reduced energy diet), prebiotics (30 g of carob/day) and probiotics (one tablet containing Bifidobacterium longum, Lactobacillus helveticus, Lactococcus lactis, Streptococcus thermophilus/ day). The three groups were matched for age, sex and BMI. Patients were seen after 1 month from the intervention. Anthropometric measures, biological parameters, dietary survey and psychological scores were performed. Results: The average age of our population was 48.73 ± 7.7 years, with a female predominance. All three groups showed a significant decrease in weight, BMI and waist circumference with p < .05. Only the prebiotic and probiotic group showed a significant decrease in fat mass ( p = .001) and a significant increase in muscle strength with p = .008 and .004, but the differences were not significant between the three groups. Our results showed also a significant decrease in insulinemia and HOMA‐IR in the prebiotic group compared to the diet‐alone group ( p = .03; p = .012) and the probiotic group showed a significant decrease in fasting blood glucose compared to the diet alone group ( p = .02). A significant improvement in sleep quality was noted in the prebiotic group ( p = .02), with a significant decrease in depression, anxiety and stress in all three groups. Conclusions: The prescription of prebiotics and probiotics with the lifestyle measures seems interesting for the management of obesity especially if it is sarcopenic, in addition to the improvement of metabolic parameters and obesity‐related psychiatric disorders. Abstract : The supplementation with prebiotics and probiotics showed an improvement in lean mass, glycaemic profile, insulin resistance and uric acid more than diet alone.